2021
DOI: 10.3390/ijerph18031362
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Perceived Helicopter Parenting, Critical Thinking Disposition, Cognitive Ability, and Learning Motivation on Learning Behavior among Nursing Students

Abstract: The purpose of this study was to determine the influence of perceived helicopter parenting, critical thinking disposition, cognitive ability, and learning motivation on learning behavior in nursing students in South Korea. The participants in this study were 149 sophomore nursing students from two universities using convenience sampling. The two universities were similar in terms of type, curricula, and size. Data were collected from October to November 2017 using self-reported questionnaires. The collected da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…There are, however, two studies that reported mixed results. Oh et al (2021) suggested that overparenting was positively related to critical thinking disposition and learning motivation in correlational analyses. But this pattern was not found in regressions.…”
Section: Resultsmentioning
confidence: 99%
“…There are, however, two studies that reported mixed results. Oh et al (2021) suggested that overparenting was positively related to critical thinking disposition and learning motivation in correlational analyses. But this pattern was not found in regressions.…”
Section: Resultsmentioning
confidence: 99%
“…Parents who control behaviors and provide excessive comforting that inhibit their child's experiences and independence in coping with stress 32 Helicopter parenting Overinvolved parents who hover around their children and solve their problems by actively intervening in their child's overall life even into adulthood 6,[33][34][35][36] Drone or snowplow parenting New terms used in popular media to describe the intensity of helicopter parenting that has grown over time, as they are described to "steamroll" or heavily manage from a distance to ensure their child's success [7][8][9][10][11][12] Young adult Individuals aged approximately 18-26 y 37…”
Section: Overprotective Parentingmentioning
confidence: 99%
“…TA B L E 1 Relevant terms and definitions defined in published research positive outcomes (eg, selecting friends who used less alcohol, less binge drinking, and fewer sexual risks 33,73 ) depending on the mediating factors (eg, parent-child affection; gender). Children of helicopter parents tend to have low self-efficacy and depend on their parents even after they become adults, which also negatively impacts their education 35,74 and the ability to adjust to living away in a university setting. 75 Helicopter parenting is a global phenomenon regardless of education, income, culture, or race 46,76,77 ; however, it has been mostly studied in Western educational/collegiate settings, 6,54,61,71,[78][79][80][81] possibly due to sample convenience.…”
Section: Emerging Adultmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the educational perspective in digital era, skills that is often mentioned as a counterpart or can be a by-product of critical thinking is problemsolving skills, which is mentioned in several researches relating mathematics learning and learnerinvolved learning. [30], [31]. According to the guidelines in promoting critical thinking, a tool that is often mentioned recently is the use of game as a learning tool, contributing to learner involvement and critical thinking skills.…”
Section: Critical Thinkingmentioning
confidence: 99%